Aplicabilidade da geoecologia das paisagens no planejamento ambiental da bacia hidrográfica do rio Palmeira-Ceará/Brasil - Farias, Juliana Felipe (2015)
The Palmeira river basin is located in the Sertões of the Centro-Norte, Ceará (longitude 41° 6 ' 31 " and latitude 3° 5 ' 14") and presents 476.87 km² area. The river basin features a variety of landscape units and of economic activities, which in certain sectors are incompatible with the ability to support natural resources. In this context, considering the Palmeira river basin as a unit of study, the present research aimed to make an proposals for environmental planning for the catchment area concerned, based on the methodological and theoretical Geoecology of the landscapes. In methodological terms, the geoecological analysis was applied in the following phases: Organization and inventory, analysis, diagnosis and purposeful. Thematic maps were prepared on a scale of 1: 160,000, aided by more detailed surveys in local scale of 1: 50,000 on use/occupation, for example. The main conclusions are possible to highlight that the basin is in a growing stage of degradation, being disturbing the estuarine area in relation to the establishment of the salt production and shrimp farming. Based on the biophysical and socioeconomic surveys conducted, in gauging environmental status, potential use and management capacity, proposals for environmental planning have been consolidated into three phases: 1) the general character; 2) a proposal for environmental zoning and functional; and, 3) aggregate integrated management strategies with the discussion of a prognosis for the basin. It is expected that the outstanding actions can contribute to the planning of the use of natural resources, in particular water, compatible with local potential. Likewise, that the main search results serve as a model for the application of Geoecology of the landscapes in other basins, with adaptations to the investigated object.